Plasmonic Au–Cu nanostructures: Synthesis and applications - Mi, Xiaohu; Chen, Huan; Li, Jinping; Qiao, Haifa (Frontiers in Chemistry, 2023)
Plasmonic Au–Cu nanostructures composed of Au and Cu metals, have demonstrated advantages over their monolithic counterparts, which have recently attracted considerable attention. Au–Cu nanostructures are currently used in various research fields, including catalysis, light harvesting, optoelectronics, and biotechnologies. Herein, recent developments in Au–Cu nanostructures are summarized. The development of three types of Au–Cu nanostructures is reviewed, including alloys, core-shell structures, and Janus structures. Afterwards, we discuss the peculiar plasmonic properties of Au–Cu nanostructures as well as their potential applications. The excellent properties of Au–Cu nanostructures enable applications in catalysis, plasmon-enhanced spectroscopy, photothermal conversion and therapy. Lastly, we present our thoughts on the current status and future prospects of the Au-Cu nanostructures research field. This review is intended to contribute to the development of fabrication strategies and applications relating to Au-Cu nanostructures.